Intercultural Communication from the Position of Linguistics, Extraling Vistics and Social Psychology - V.A. Kornev; O.V. Murashkina (Язык и текст, 2021)
Cross-cultural communication is communication between representatives of different cultures, regardless of what field they communicate in. Now, when the mixing of peoples, the interpenetration of languages and cultures, the migration of population flows have reached an unprecedented scale, the problem of coexistence in a multicultural space, the dialogue of cultures, the education of tolerance for foreign cultures, the awakening of interest and respect for them, the overcoming of xenophobia, racism, nationalism and chauvinism is more acute than ever. This is the reason for the general increase in attention to intercultural communication, the study of its linguistic, sociological, psycholinguistic and other aspects.To date, research in the field of intersubject communication has focused on the behavior of people who encounter differences in language activity and the consequences of these differences. Most often, intersubject communication is interpreted as an adequate mutual understanding of communication participants belonging to different national cultures. Cross-cultural communication skills are necessary for those whose professional activities are directly related to the interaction between cultures and are carried out through communication. These include education, socio-political, translation, management, consulting, social work, journalism, business, etc. In recent years, increased interest not only in scientific circles, but also among the general public has attracted the problem of tolerance education. The main reasons for increasing attention to this problem are globalization, migration and socio-economic problems. In these conditions, the priority task is to address the problem of fostering tolerance in the younger generation.